2015
DOI: 10.5604/12321966.1185765
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological study of Lyme disease among high-risk population groups in eastern Slovakia

Abstract: Introduction and objective. The aim of the presented cross-sectional sero-epidemiological study was to determine the current presence of antibodies against B. burgdorferi s.l. in the high-risk groups of the Slovak population, and to identify potential risk factors to LB infections. Materials and method. A group of 277 agricultural and forestry workers -persons with frequent stay in the countryside and employees of State Border and Customs Police -from years 2011-2012 in the Eastern Slovakia were examined in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
4
13
0
3
Order By: Relevance
“…In the study conducted at the same University among students of the tourism and recreation faculty, episodes of tick bite were declared by 55.4% [8], and in research among young people from this region of Poland -58.9% [9]. In the study in eastern Slovakia, a history of the tick bite was reported in 37.3% of healthy blood donors [10] and in 87.0% of persons exposed to tick bite [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted at the same University among students of the tourism and recreation faculty, episodes of tick bite were declared by 55.4% [8], and in research among young people from this region of Poland -58.9% [9]. In the study in eastern Slovakia, a history of the tick bite was reported in 37.3% of healthy blood donors [10] and in 87.0% of persons exposed to tick bite [11].…”
Section: Discussionmentioning
confidence: 99%
“…Obszar wschodniej Polski (województwo lubelskie) i zachodniej Ukrainy (okolice Tarnopola) są uznane za obszary endemicznego występowania boreliozy z Lyme, zatem problem tej choroby dotyczy ich w podobnym stopniu. Zarówno w Polsce, jak i na Ukrainie ryzyko wystąpienia tej choroby jest wyższe wśród pracowników leśnych oraz osób aktywnych hobbystycznie na obszarach leśnych i w ich okolicach − myśliwych, turystów oraz zbieraczy runa leśnego [1,9]. Na Ukrainie przeciwciała anty-B.…”
Section: Wstępunclassified
“…Zákutná i wsp. [9] wykazali, że wśród osób narażonych na pokłucia przez kleszcze we wschodniej Słowacji 51% respondentów używa repelentów w celu zmniejszenia ryzyka pokłucia. W badaniach Buczek i wsp.…”
Section: Omówienieunclassified
“…Contact with insects, ticks and other animals may be equally perilous, and the substances produced by them: faeces, saliva, blood, venom, are especially dangerous. Also, biological hazards concern the possibility of allergy or poisoning with substances produced by plants or infection with the germs of zoonoses, such as borreliosis (Lyme disease), rabies, tickborne encephalitis and meningitis, or tularemia [17,18,19]. Biological factors occurring in forestry include also the occurrence of allergy of the upper airways as a result of exposure to filamentous fungi, some structures and substances produced by trees (pollens, essential oils, resins), as well as allergens of some caterpillars feeding on trees, or dermatitis as caused by contact with liverworts or lichens [16,20,21,22].…”
Section: Hazards In the Public Sector Of Forestrymentioning
confidence: 99%